Philosophical analysis of Mortimer J. Adler's Christian education and global education management - Sanasintani, Sanasintani; Munte, Alfonso (Journal of Education and Learning (EduLearn), 2024)
The present research shows the absurdity of education, especially education management, in the posthumanist schema. Posthumanists seem to want to form their own group, but researchers see that posthumanism is not new, especially in the world of education. Philosopher Mortimer J. Adler, in the framework of perennialism, shows the structure of education, especially in America, which, according to researchers, is relevant in Indonesia. Research findings are based on qualitative research with data retrieval methods from literature studies. Results showed that Mortimer J. Adler's philosophical thinking emphasizes the expansion of education management in both depth and fragility by and through learners, parents, teachers and related parties in the mecca of an independent curriculum.